Epstein-Barr Virus Infection in Children: Improving the Diagnosis and Treatment Program - E. N. Simovanyan; V. B. Denisenko; A. V. Grigoryan; M. A. Kim; L. F. Bovtalo; L. V. Belugina (LLC "Diagnostics and Vaccines", 2016)
Widespread, severe course, frequent development of chronic forms, adverse effects of the Epstein-Barr virus infection to the health of children, the difficulties of diagnosis and therapy dictate the need to improve the diagnostic and treatment programs in this disease. A total of 286 patients with acute and chronic Epstein-Barr virus infection. It was established, that for the timely diagnosis of the disease requires a comprehensive analysis of anamnesis, clinical symptoms, including symptoms of acute and chronic mononucleosis syndrome in combination with multiorgan pathology, and the results of laboratory examination (enzyme immunoassay, polymerase chain reaction, immune status).